“Os donos da aldeia”: história, memória e mobilização étnica do povo Tabajara da Paraíba - Cruz, Amandda Yvnne Figueiredo da (2022)
In the year 2006, a group of people who identified themselves as the "Caboclo Family" approached the National Indian Foundation, stating that they had ancestral land in the municipality of Conde, Paraíba, known as "Sítio dos Caboclos," and that it had been forcibly taken away in the mid-20th century, leading to the dispersal of the domestic groups living there. The demand of the Caboclo Family to the FUNAI and other public institutions led to a series of studies that identified their ancestral relationship with the Tabajara indigenous people who inhabited the southern coast of Paraíba and were settled in the Jacoca/Conde and Arataguy/Alhandra villages. These indigenous people lived in these villages until the 1860s when they were unilaterally declared extinct by the imperial government of Brazil and became subject to a policy of forced land allocation, which led to a period of intense dispossession and deterritorialization. Based on the case of the Tabajara people, the work seeks to understand the paths of disappearance of indigenous populations living in villages and how this group resurfaced in the 21st century, seeking historically denied rights. Through micro-history, family trajectories and genealogies of some indigenous people living in villages were reconstructed, as well as the usurpation of the "Sítio dos Caboclos" and the genealogical lines that gave rise to the extended family in the area. The distribution of power in the municipality of Conde, the stage of the current Tabajara ethnic mobilization, was described from the 1960s onwards. Finally, the mobilization led by the Tabajara families was analyzed, focusing on their right to return to the traditional territory and the process of fighting for the redefinition of social control over the territory's environmental resources.